Glucose and Leucine Metabolism in Lung Tranplanted Patients on Low Dose of Steroids for Immunosuppressive Therapy - Benedini, S.; Ruffini, E.; Terruzzi, I.; Mancuso, M.; Luzi, L. (Transplantation proceedings, 2008)
This study examined the metabolic effects of lung transplantation in patients with end-stage respiratory failure on low dose of steroids for immunosuppressive therapy. We examined 6 patients, including 2 women and 4 men of overall mean age 53 ± 15 years and age at transplantation 34 ± 12 months, receiving cyclosporine 5.73 ± 1.43 mg/kg/d or tacrolimus (FK 506) 4.67 ± 0.58 mg/d, azathioprine 0.47 ± 0.29 mg/kg/d, and prednisone 8.25 mg/d for comparison with 6 healthy subjects, who were selected to be comparable to the recipients in terms of anthropometric features and age. A euglycemic hyperinsulinemic clamp (1 mU/kg/min) associated with infusion of glucose and leucine isotopes was performed with indirect calorimetry. Lung transplanted patients showed postabsorptive leucine and free fatty acid metabolism similar to controls. In contrast, there was peripheral insulin resistance with respect to glucose metabolism namely, higher values of glucose and insulin vs controls ( P < .03 and P < .02, respectively). During the clamp the metabolic picture was characterized by a relative insulin resistance with respect to glucose metabolism ( P = .07). Lipid and protein metabolism in the basal and insulin-stimulated conditions were similar to the control group. In the basal condition insulin resistance is evident with respect to glucose metabolism. The metabolic picture in lung transplanted patients on low-dose steroid therapy was characterized by normal insulin-stimulated glucose, leucine, and free fatty acid metabolism. The minimal metabolic alterations in these patients were not due to transplantation itself but probably mainly attributable to immunosuppressive therapy.